"We Think You'll Make a Great Fit": Navigating the Precarity of Being a Gay International Teacher. Issue 3 (3rd July 2022) - Brady, Brian
ABSTRACT: LGBTQ+ teachers are an understudied and overlooked population in educational research, especially in the nascent field of international teacher studies. International teachers must contend with new kinds of precarity than they are used to in their home countries, and these kinds of precarity are more threatening to LGBTQ+ and BIPOC teachers. This paper is a call to recognize not only the experiences of LGBTQ+ teachers in the international teaching community, but also the heteronormative and racial biases that come into play in the hiring of teachers, both in the United States and international schools.